Allergic contact dermatitis to enema used to treat inflammatory bowel disease - Maria J. Guimarães; Ana G. Lopes; Teresa Pereira (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Enemas are commonly used to treat inflammatory bowel disease. It is believed that allergic contact dermatitis (ACD) to enemas is underreported. We describe a case of a 55-year-old woman with non-specific proctitis. The patient was prescribed budesonide rectal enemas. However, 1 day after the first application, erythematous, pruritic plaques emerged in the perineal region and inner thighs. The patient was observed in the emergency department and was ordered to stop the enemas. The patient was referred to dermatology consultation where patch tests were performed using the European/Portuguese baseline series, the corticosteroids series, and the dispersible tablets of budesonide used in the enema. Test readings at 72 h and 7 days revealed positivity for budesonide 0.01% pet, tixocortol pivalate 0.1%, the budesonide tablets used in enemas, perfume mixture 1 (8% pet) and 2 (14% pet) and hydroperoxides of linalool 1%. No lesions have recurred after eviction of the identified allergens. Budesonide is responsible for most ACD to corticosteroids, usually described in association with inhalers or nasal sprays to treat asthma or rhinitis. According to the new classification of corticosteroids by allergenic groups, budesonide, and tixocortol pivalate belong to the same group. Facing a patient with corticosteroid allergy, it is important to determine the individual sensitization/tolerance profile to guide future therapeutic interventions.